Firm Value and Hedging: Evidence from U.S. Oil and Gas Producers - JIN, YANBO; JORION, PHILIPPE (Journal of Finance, 2006)
ABSTRACT This paper studies the hedging activities of 119 U.S. oil and gas producers from 1998 to 2001 and evaluates their effect on firm value. Theories of hedging based on market imperfections imply that hedging should increase the firm's market value (MV). To test this hypothesis, we collect detailed information on the extent of hedging and on the valuation of oil and gas reserves. We verify that hedging reduces the firm's stock price sensitivity to oil and gas prices. Contrary to previous studies, however, we find that hedging does not seem to affect MVs for this industry.